THE PRINCIPAL’S MANAGERIAL ABILITY IN DEVELOPING EFFECTIVE SCHOOLS - Khusni, Wasial; Mahmudah, Fitri Nur (International Journal of Educational Management and Innovation, 2020)
School is one of the educational institutions where the teaching and learning process takes place to educate the nation's generation. As a leader, the principal plays an essential role in determining policy. The policy was the aim to make schools more competitive. For this reason, the principal must be able to develop it into an effective school. The purpose of this study is to know the principal's managerial abilities in developing effective schools. This research uses a qualitative method and descriptive approach, analyzed using Analysis Interactive. The results of this study that school managerial ability in developing effective schools are by following the procedures, first, planning programs include; the planning process; and the strategy of designing program planning. Second, the program implementation, including; sharing tasks and routine explanation regarding work and responsibilities, building communication with all school residents properly, motivation colleagues to work effectively and efficiently in achieving goals, running managerial based on school management guidelines, managing human resources, managing relationships with parents and society, overcoming constraints in managerial. Third, program evaluation, including; evaluation methods, follow-up programs, matters discussed in evaluation, and influence perceived after evaluation.